Quantitation of α1A and α1D-adrenoceptor mRNA in prostate tissues from patients with symptomatic benign prostatic hyperplasia - Acharya, B; Okada, H; Aryal, G; Shirakawa, T; Hinata, N; Gotoh, A (Journal of Pathology of Nepal, 2011)
Background: To treat symptomatic benign prostatic hyperplasia α1-adrenoceptor antagonists with little antagonism at α1b-adrenoceptor were used to avoid orthostatic hypotension. In benign prostatic hyperplasia tissues α1D-adrenoceptor are thought to predominate, but in the Japanese experience, either α1A- or α1D- adrenoceptor antagonists can alleviate benign prostatic hyperplasia symptoms. We hypothesized that prostatic expression of α1A- and α1D-adrenoceptor varies quantitatively between patients. Materials and Methods: We immunohistochemically localized α1A- and α1D-adrenoceptor within benign prostatic hyperplasia tissues, and quantitated mRNA expression for these subtypes by real-time quantitative reverse transcription-polymerase chain reaction. Results: Immunohistochemistry detected both subtypes in stromal but not detected epithelial cells. Copy numbers of α1A-adrenoceptor mRNA in benign prostatic hyperplasia tissue were significantly higher than those of α1D-adrenoceptor mRNA. Among patients; the ratio of α1A- to α1D-adrenoceptor mRNA ranged from 1.0 to 8.4. Conclusion: An ideal therapeutic antagonist for treating benign prostatic hyperplasia symptoms should block both α1A- and α1D-adrenoceptor Keywords: Adrenoceptor subtypes; Benign prostatic hyperplasia; Quantitative reverse transcription-polymerase chain reaction DOI: 10.3126/jpn.v1i1.4439 Journal of Pathology of Nepal (2011) Vol.1, 1-7